Le Courtier d’assurances face à la responsabilité professionnelle - Laberge, Gérald (Assurances)

(untitled) (HEC Montréal, 1989)
At a time when the Quebec insurance industry is undergoing major changes due ta decompartmentalization, the role of the broker takes on more and more importance. The author, himself a broker, explains the very varied roles the insurance broker must play in his day-to-day activities. The lack of examples dealing with case law is volontary on his part; instead he uses actual experiences to make his point. Indeed, the broker renders numerous services to his client, notably helping him analyse the risks he faces, by assisting in choosing from among the coverages available on the market and, more important, by defending his interests at all times.